Integrated microRNA and mRNA expression profile analysis of tumor-associated macrophages after exposure to single-dose irradiation. (June 2018) - Kung, Wei-Hsiang; Lee, Chi-Lung; Yang, Chi-Dung; Yu, Ching-Fang; Chiew, Men-Yee; Chen, Fang-Hsin; Huang, Hsien-Da
Abstract: Background: Radiotherapy (RT) is a common approach that accounts for nearly 50% of cancer patient treatment and has the potential for long-term tumor control. Recently, we published a research article on gene expression profiling of tumor-associated macrophages (TAM) that were exposed to ionizing radiation (IR). Single-dose irradiation of tumors could initiate differentially expressed genes in TAM as a time series from irradiated tumors that are associated with the immune response. It is also well known that human cancers are associated with microRNA (miRNA) alterations that are involved in cancer progression. However, the role of miRNA on TAM after exposure to irradiation remains unclear. Results: In this study, miRNA expression profiles from microarrays were used to identify the key miRNAs and correlating pathways involved in the role of TAMs in tumor progression and recurrence after RT. Using a mouse tumor model, we identified miRNA pattern changes over time in response to irradiation. Based on our results, we hypothesize that miRNA expression in the irradiated tumor may be used as a distinguishing marker to indicate the best time for therapeutic intervention to prevent tumor recurrence after RT. Conclusions: We established a murine model irradiated with a single dose of 25 Gy that could initiate temporal changes in the expression of miRNAs associated with cell proliferation and the immune response, as evidenced by macrophages directly extracted from irradiated tumors after two weeks of IR. Statistical analyses were conducted by comparing the miRNA expression in macrophages from non-irradiated versus irradiated tumors. Thus, our study could lead to a better understanding of the function of miRNA expressions, which changed temporally in an irradiated tumor microenvironment.